2019
DOI: 10.1001/jamanetworkopen.2019.9535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Primary Care Parent-Targeted Interventions on Parent-Adolescent Communication About Sexual Behavior and Alcohol Use

Abstract: This randomized clinical trial evaluates the efficacy, feasibility, and acceptability of a parent-targeted intervention for parent-adolescent communication about sexual health and alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Another recent study found that positive parent–adolescent communication was positively associated with the level of youths’ subjective well-being and negatively associated with rejection sensitivity [ 31 , 32 ]. Specifically, adolescents with parental support and strong family relationships tend to initiate conversations with their parents, instead of showing high rejection sensitivity after being cyberbullied, thereby lessening the impact of negative events [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study found that positive parent–adolescent communication was positively associated with the level of youths’ subjective well-being and negatively associated with rejection sensitivity [ 31 , 32 ]. Specifically, adolescents with parental support and strong family relationships tend to initiate conversations with their parents, instead of showing high rejection sensitivity after being cyberbullied, thereby lessening the impact of negative events [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce these barriers, there needs to be a concerted effort to ensure that parents and guardians have the right information and training to know how and when to talk to their children about sex and contraception. Evidence-based educational efforts are necessary to ensure parents and guardians have the tools to fulfill this important function [ 21 , 22 ]. At a clinical and policy level, it is essential to ensure that women have access to affordable or no-cost contraception at any age.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who did have knowledge about reproductive health matters were 2.91 times likely to communicate SRH issues with their parents compared with those who did not have knowledge about reproductive health issues (OR = 2.91, 95% CI:1.21, 7.01). Knowledge on reproductive health matters was also reported to be statistically significant with parent-adolescent communications on SRH issues in an intervention study by Ford et al The study indicated that adolescents in the sexual health intervention group reported a higher mean frequency score for parent-adolescent communication about sex compared with control counterparts [ 33 ]. Similarly, believe on the importance of discussion on SRH issues was found to be the predictor of parent-adolescent communication on SRH issues in in this systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%